2019
DOI: 10.1039/c9ob00690g
|View full text |Cite
|
Sign up to set email alerts
|

Photorearrangement of dihetarylethenes as a tool for the benzannulation of heterocycles

Abstract: The photochemical rearrangement of dihetarylethenes is a powerful tool for the benzannulation of heterocycles, providing a wide scope of benzannulated heterocycles and N-, S-, C-, and O-substituents in the newly formed benzene ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 84 publications
0
21
0
Order By: Relevance
“…However, inert conditions were used in one of them, and no preparative synthesis was performed in another one (Scheme ). Efficient preparative reaction of cyclopentenone-based diarylethene 37c (Scheme ) in aerobic conditions became the starting point for a series of works , where the photorearrangement of diarylethenes 41 with cyclopentenone and furanone bridges was studied (Scheme ). Derivatives of benzene, naphthalene, and various heterocycles were used as the aromatic moieties whose nature determined the photolysis conditions.…”
Section: Blocking the Oxidation/elimination Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inert conditions were used in one of them, and no preparative synthesis was performed in another one (Scheme ). Efficient preparative reaction of cyclopentenone-based diarylethene 37c (Scheme ) in aerobic conditions became the starting point for a series of works , where the photorearrangement of diarylethenes 41 with cyclopentenone and furanone bridges was studied (Scheme ). Derivatives of benzene, naphthalene, and various heterocycles were used as the aromatic moieties whose nature determined the photolysis conditions.…”
Section: Blocking the Oxidation/elimination Processesmentioning
confidence: 99%
“…Photolysis of β-substituted thiophene derivatives gives ethenetiol derivatives that are rather unstable, which in certain cases results in hydrolysis to afford carbonyl derivatives . These compounds can be stabilized using in situ alkylation with alkyl halides in the presence of potassium carbonate (Scheme , reaction II) . Photorearrangement of β-substituted furan derivatives gives relatively stable carbonyl compounds (reactions III) .…”
Section: Mechanism Of Photoinduced Rearrangementmentioning
confidence: 99%
“…While studying the related reaction of the photorearrangement of diarylethenes with the formation of naphthalene derivatives, we also encountered some facts that do not fit the traditional concepts about the mechanism of this reaction. Specifically, it was found that the photocyclization of some diarylethenes containing a methyl substituent at the ring-closing position leads to the formation of a phenanthrene analogue along with breaking of a strong C–C-bond (abstraction of the methyl group) . In another example, the photocyclization of diarylethene, which is free of substituents at the ring-closing position, results in a sigmatropic shift followed by opening of the benzene ring under aerobic conditions …”
Section: Introductionmentioning
confidence: 99%
“…Among the plethora of more or less recent methods, benzannulation has been surely less practiced with respect to heteroannulation. Actually, classic syntheses tend to build up the penta-atomic heteroring, exploiting the functionalities of properly derivatized benzene substrates [4], rather than assembling the hexa-atomic ring onto a pyrrolic starting material [4,5,6]. Only in recent years, some examples of benzannulating procedures in which a C 4 building block is involved have been reported: an approach to be generally preferred when specific substituents are needed at the 4–7 positions, as they can be conveniently placed in the appropriate positions of the employed reagent.…”
Section: Introductionmentioning
confidence: 99%